Gut Microbiota and Neurotransmitter Regulation: Functional Effects of Four Traditional Chinese Fermented Soybean (Sojae Semen Praeparatum) - Lin Zhang; Huo Su; Siqi Wang; Yujie Fu; Manyuan Wang (Foods)
This study aims to evaluate the potential disease prevention and treatment functions of four types of traditional Chinese fermented Sojae Semen Praeparatum (SSP) by analyzing their nutritional active components and their effects on the gut microbiota. Raw soybeans and the four SSPs were administered as dietary supplements to normal SD rats for 6 weeks. Fecal samples were collected at weeks 0, 2, and 6 to assess changes in the gut microbiota. Our results revealed that different fermentation methods resulted in variations in soybean isoflavone content. Fermented soybeans promoted the growth of beneficial microorganisms associated with short-chain fatty acid production in the gut microbiota, such as Christensenellaceae_R_7_group, compared to unfermented soybeans. Supplementation with SSPs fermented with different processes increased the diversity of the rat gut microbiota, except for the fermented group of qingwenjiedu decoction (QW). The dominant gut microbiota in the fermented group of Artemisia Annuae Herba and Mori Folium (QS) exhibited anti-inflammatory effects, while the dominant gut microbiota in the fermented group of Ephedrae Herba and Perillae Folium (MZ) showed antidepressant effects. In the neurotransmitter analysis, MZ reduced gamma-aminobutyric acid (GABA) levels, the fermented group without Chinese medicine (DD) decreased dopamine levels, and both QS and QW increased norepinephrine levels. Correlation analysis highlighted connections between gut microbiota, neurotransmitters, and chemical levels. The results indicate that SSPs may contribute uniquely to health by maintaining intestinal balance and improving neurological disorders while predicting a potential association between neurotransmitters and gut microbiota by correlation analysis.